2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.154-344
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of Autonomic Regulation Behaviour Using Short:Term Cross:Spectral Analysis on RR and QT Intervals

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For time-domain analysis, the following parameters were taken into account: mean value of RRI (RRI, ms), the standard deviation of the mean of all sinus rhythm R-R intervals (SDNN, ms), square root of the mean of the squared differences between successive R-R intervals (root-mean-square successive difference, rMSSD) and percentage of differences between successive R-R intervals that are greater than 50 ms on overall normal beats (pNN50, %). For frequency-domain analysis, autoregression (AR) model was used for power spectrum density estimation ( Zhan et al, 2016 ). The following parameters were calculated: low frequency (0.04–0.15 Hz) spectral power (LF); high frequency (0.15–0.40 Hz) spectral power (HF); and LF/HF ratio (LF/HF).…”
Section: Methodsmentioning
confidence: 99%
“…For time-domain analysis, the following parameters were taken into account: mean value of RRI (RRI, ms), the standard deviation of the mean of all sinus rhythm R-R intervals (SDNN, ms), square root of the mean of the squared differences between successive R-R intervals (root-mean-square successive difference, rMSSD) and percentage of differences between successive R-R intervals that are greater than 50 ms on overall normal beats (pNN50, %). For frequency-domain analysis, autoregression (AR) model was used for power spectrum density estimation ( Zhan et al, 2016 ). The following parameters were calculated: low frequency (0.04–0.15 Hz) spectral power (LF); high frequency (0.15–0.40 Hz) spectral power (HF); and LF/HF ratio (LF/HF).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study [6], we applied cross-spectrum method, measuring the linear coupling of RRI and QTI, to characterize alterations in ANS behaviors of those with high risk for cardiac arrhythmias and sudden cardiac death. We have shown that by directional correlation analysis of RRI and QTI based on transfer function.…”
Section: Introductionmentioning
confidence: 99%